RETRACTED: REGULATION OF CELL GROWTH AND KI-67 EXPRESSION BY GHRELIN: ANALYSIS OF PRIMARY BRAIN TUMOR CELL LINES: The article has been retracted at the request of the corresponding author due to concerns regarding the authenticity and integrity of the data. These concerns include ‘data fabrication or manipulation’’. In accordance with COPE (Committee on Publication Ethics) guidelines, the journal has retracted the article to maintain the integrity of the scientific record. - Javed, Sumaira; Afridi, Muhammad Kabir Khan; Hameed, Nadira; Sadaf, Aisha; Khattak, Khabeer Ahmad; Humayun, Sidra (Khyber Journal of Medical Sciences, 2025)
Objective: The current study aimed to determine the proliferative effect of ghrelin on primary brain tumor cell lines. Methodology: A laboratory-based experimental study was designed and performed in the Department of Anatomy, Khyber Medical University, Peshawar. Three Primary brain tumor cells i.e., glioma, glioblastoma, and meningioma, samples were obtained from patients after craniotomy. Cell lines (IK148, IK155, and IK169) were established and treated with ghrelin (0-400nM). Cell migration and proliferation were assessed through wound closure assays while Ki-67 expression was analyzed using immunofluorescence. Results: Treatment with 20 nM ghrelin significantly enhanced tumor cell proliferation, with complete wound closure observed within 72 hours in the scratch assay. Higher ghrelin concentrations (>20nM) showed reduced migration, with incomplete wound closure even after 6 days. Immunofluorescence analysis demonstrated that cells treated with 20nM ghrelin exhibited markedly elevated Ki-67 expression, indicating enhanced proliferation, while those exposed to 50nM ghrelin showed minimal Ki-67 expression." Conclusion: Ghrelin hormone has a proliferative effect on brain tumor cells in low concentration (20 nM). Higher concentrations of ghrelin up to 50nM have anti-proliferative effects.